A systematic review of approaches to dental care in head and neck cancer patients - Rebecca Doctor; Tapan Padhya; Matthew Mifsud; Christopher Nickel (Oral Oncology Reports)
There are well documented challenges related to dental care in the head and neck cancer population. Perioperative management of dental disease is critical, especially for patients requiring adjuvant radiation therapy. Head and neck cancer patients in the United States often have limited or no access to dental care. As a result, head and neck surgeons may be the sole practitioners able to deliver dental care. This paper summarizes the existing literature on dental care for head and neck cancer patients and outlines a streamlined approach to the perioperative management of dental disease.